COMPARISON OF ABDOMINOPERINEAL PROCTOPLASTY TECHNIQUES IN CHILDREN WITH HIRSCHSPRUNG’S DISEASE ACCORDING TO THE CLAVIEN–DINDO CLASSIFICATION - Ochildiyev Islombek Amanbek ogli (Web of Journals Publishing, 2026)
This article compares the outcomes of two types of abdominoperineal proctoplasty—Soave–Boley and Soave–Lenyushkin techniques—in children with Hirschsprung’s disease based on the Clavien–Dindo classification of surgical complications. Analysis of complication severity allows for an objective assessment of surgical safety. According to the obtained results, most complications in the Soave–Boley group corresponded to Clavien–Dindo grades I–II, whereas grade III complications were relatively more frequent in the Soave–Lenyushkin group. The Clavien–Dindo classification proved to be a reliable and reproducible method for comparing surgical techniques. The article was based on archival records from 2010 to 2025 and the authors’ own clinical observations conducted at the Department of General Surgery of the Khorezm Regional Multidisciplinary Children’s Medical Center and the Department of General Surgery of Urgench State Medical Institute.
Keywords: Hirschsprung’s disease, abdominoperineal proctoplasty, Soave–Boley, Soave–Lenyushkin, Clavien–Dindo, pediatric surgery, complications.